2019
DOI: 10.1186/s40425-019-0744-4
|View full text |Cite
|
Sign up to set email alerts
|

BTLA blockade enhances Cancer therapy by inhibiting IL-6/IL-10-induced CD19high B lymphocytes

Abstract: BackgroundThe standard treatment for epithelial ovarian carcinoma (EOC) is surgery followed by platinum/paclitaxel-based chemotherapy, but the overall survival rate is poor. The purpose of this study was to investigate the therapeutic potential of chemotherapy combined with inhibition of B and T lymphocyte attenuator (BTLA) for clinical use to treat EOC.MethodsInitially, we evaluated the potential application of chemotherapy combined with anti-BTLA antibody in an animal model. We then analyzed the distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 52 publications
(76 reference statements)
3
63
1
Order By: Relevance
“…Studies established the singular role of BTLA as both co-stimulator and co-inhibitor to activated cancerous CD8 + T cells (Derre et al, 2010;Ritthipichai et al, 2017). The clinical trial in which the registration number was NCT00854399 revealed that BTLA detected in epithelial ovarian carcinoma (EOC) tissues can predict poor outcomes of patients, and chemotherapy combined with BTLA inhibitor can enhance immune activation and produces effective anti-tumor effects (Chen Y. L. et al, 2019). So far, it remains inconclusive about the mechanism of BTLA in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Studies established the singular role of BTLA as both co-stimulator and co-inhibitor to activated cancerous CD8 + T cells (Derre et al, 2010;Ritthipichai et al, 2017). The clinical trial in which the registration number was NCT00854399 revealed that BTLA detected in epithelial ovarian carcinoma (EOC) tissues can predict poor outcomes of patients, and chemotherapy combined with BTLA inhibitor can enhance immune activation and produces effective anti-tumor effects (Chen Y. L. et al, 2019). So far, it remains inconclusive about the mechanism of BTLA in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…BTLA is a negative regulator of BCR signaling that is downregulated after B cell activation [ 32 , 41 ]. Furthermore, BTLA + CD19 hi B cells were associated with poor outcome in ovarian cancer [ 42 ]. GITR expression in human B cells has not been reported before, but studies in mice revealed a weak expression, which was increased by activation of BCR and CD40 and suppressed by cytokines secreted from T cells [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the co-expression of MHC class II on tumor cells and LAG-3 on CD8 REP-TILs is a potential limitation for the anti-tumor reactivity of REP-TILs and suggests that the addition of an anti-LAG-3 blocking antibody might be beneficial in these patients. Similarly, the importance of BTLA in the microenvironment of ovarian cancer has recently been reported [36] and, though the immune regulatory pathway might be more complex, anti-BTLA therapy might also be beneficial in ACT [37]. Still, two patients showed no tumor expression of MHC class I or II which could limit the tumor recognition and T cell reactivity altogether.…”
Section: Discussionmentioning
confidence: 89%